2020
DOI: 10.3389/fmicb.2019.03146
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Lactobacillus gasseri and Lactobacillus crispatus Isolated From Human Urogenital and Gastrointestinal Tracts

Abstract: Lactobacillus crispatus and Lactobacillus gasseri are two of the main Lactobacillus species found in the healthy vaginal microbiome and have also previously been identified and isolated from the human gastrointestinal (GI) tract. These two ecological niches are fundamentally different, notably with regards to the epithelial cell type, nutrient availability, environmental conditions, pH, and microbiome composition. Given the dramatic differences between these two environments, we characterized strains within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 60 publications
(67 reference statements)
6
45
1
Order By: Relevance
“…Additionally, changes occurred often in the unknown function (S) and unassigned (NA) groups. These changes have been noted in other studies as well [23]. In contrast to genetic changes, which primarily occurred early on (most SNPs detected by generation 50), it appears most transcriptional impact was detected at later generations, suggesting a more significant impact over time on the transcriptome than the genome (Table 4).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Additionally, changes occurred often in the unknown function (S) and unassigned (NA) groups. These changes have been noted in other studies as well [23]. In contrast to genetic changes, which primarily occurred early on (most SNPs detected by generation 50), it appears most transcriptional impact was detected at later generations, suggesting a more significant impact over time on the transcriptome than the genome (Table 4).…”
Section: Discussionsupporting
confidence: 69%
“…To date, the primary concept underlying protection of the vaginal environment by Lactobacillus species colonization is competitive exclusion [33], which presumably hinges on the ability of these strains to survive and grow in the vaginal environment. Therefore, we began our analyses by comparing strain growth in MRS (primary defined medium for Lactobacillus species growth in a laboratory setting) and SVF [23]. As anticipated, all strains grew well in MRS and did not showcase altered growth in this medium over the time course of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the differences in the genetic information inherent in L. crispatus isolated from different niches remain unclear. Recently, comparative genomics of two L. crispatus strains from the vagina and feces showed that the two isolates differed slightly in terms of genomic size, exopolysaccharides, and CRISPR-Cas system [19]. However, this work did not reveal the genetic relationships of strains from different habitats, and only focused on limited number of strains.…”
Section: Introductionmentioning
confidence: 96%
“…L. gasseri has been described as a multifunctional probiotic and one of the dominant species in the human intestine [ 62 ]. These microorganisms can be isolated from human feces, breast milk, urogenital tract, and oral cavity [ 64 , 103 , 104 ]. Several health benefits were attributed to this probiotic through antimicrobial activity and immunomodulation [ 62 ].…”
Section: Probiotics and Immunitymentioning
confidence: 99%
“…Recently, lactobacilli were isolated from human feces, and thirteen were identified as L. gasseri by 16 rDNA sequencing, showing the genetic diversity and different probiotic characteristics [ 105 ]. The resistance of L. gasseri to the human gastrointestinal tract under difficult conditions is a property that allows this microorganism to colonize the gut, improving the microbiome [ 103 , 106 ]. A recent study showed that L. gasseri PA3 modulated the diversity of the microbiota after in vitro fermentation, increased the relative abundance of Lactobacillus and Escherichia, and decreased Bacteroides and Phascolarctobacterium [ 70 ].…”
Section: Probiotics and Immunitymentioning
confidence: 99%